Qualitative and Quantitative Analysis of the Major Bioactive Components of Juniperus chinensis L. Using LC-QTOF-MS and LC-MSMS and Investigation of Antibacterial Activity against Pathogenic Bacteria - Da Jung Lim; Jeong-Sup Song; Byoung-Hee Lee; Youn Kyoung Son; Yangseon Kim (Molecules, 2023)
Plants in the genus Juniperus have been reported to produce a variety of chemical components, such as coumarins, flavonoids, lignans, sterols, and terpenoids. Here, ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS) and ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) were applied to qualitatively and quantitatively analyze the major bioactive components in an ethanolic crude extract from the leaves of Juniperus chinensis L., which grows naturally in Korea. In addition, the antibacterial activity of the crude extract against pathogenic bacteria was investigated. Using LC-QTOF-MS analysis, we identified ten compounds, of which six were confirmed to be flavonoid and lignan-based components as the major bioactive components, i.e., isoquercetin, quercetin-3-O-α-l-rhamnoside, hinokiflavone, amentoflavone, podocarpusflavone A, and matairesinoside. Among them, a quantitative analysis performed using LC-MS/MS revealed that the levels of quercetin-3-O-α-l-rhamnoside and amentoflavone in the crude extract were 203.78 and 69.84 mg/g, respectively. Furthermore, the crude extract exhibited potential antibacterial activity against 10 pathogenic bacteria, with the highest antibacterial activity detected against Bordetella pertussis. Thus, further studies of the leaf extract of J. chinensis L. must be carried out to correlate the compounds present in the extract with the antibacterial activity and elucidate the mechanisms of action of this extract against bacteria.